2018
DOI: 10.1096/fj.201801855r
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia promotes microvillus membrane expression of DMT1 in intestinal epithelial cells in a PKCα‐dependent manner

Abstract: Excessive iron increases the incidence of diabetes and worsens diabetic complications. Reciprocally, diabetes induces iron loading, partially attributable to elevated intestinal iron export according to a recent report. Herein, we show that iron uptake and the mRNA expression of iron importer divalent metal transporter 1 (DMT1) were significantly increased in the duodenum of streptozotocin‐induced diabetic mice. Immunofluorescence staining of human intestinal biopsies revealed increased brush border membrane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…Zhao et al have found out that hyperglycemia in a PKCα-dependent manner inhibits the ubiquitination, internalization and degradation of the divalent metal transporter 1 (DMT1) present on the microvillar membranes of IECs. Subsequently, intestinal iron uptake is enhanced and accumulated iron ions aggravate diabetes-related complications and increase mortality (82,83).…”
Section: Gastrointestinal Tract (Git)mentioning
confidence: 99%
“…Zhao et al have found out that hyperglycemia in a PKCα-dependent manner inhibits the ubiquitination, internalization and degradation of the divalent metal transporter 1 (DMT1) present on the microvillar membranes of IECs. Subsequently, intestinal iron uptake is enhanced and accumulated iron ions aggravate diabetes-related complications and increase mortality (82,83).…”
Section: Gastrointestinal Tract (Git)mentioning
confidence: 99%
“…Liu et al (2012) observed that the selective inhibition of PKC-β, improved left ventricular function and structure in a diabetes animal model of streptozotocin-injected rats. More recently, it was reported that the activation of PKC-α in the intestine of streptozotocin-induced diabetic mice contributed to the enhanced uptake of iron leading to iron loading that contributes to diabetic complications (Zhao et al, 2018). Furthermore, the inhibition of PKC-ζ was shown recently to improve insulin sensitivity and uptake of glucose in rat adipocytes rendered insulin-resistant by incubating them in high glucose and high insulin concentrations (Lu et al, 2018).…”
Section: Endothelial Dysfunction and Hyperglycemia: Key Molecular Dismentioning
confidence: 99%
“…The divalent metal transporter (SCL11A2/DMT1) is located on the apical surface of the enterocyte and is involved in the intestinal Fe uptake [19]. SLC11A2/DMT1 gene expression is upregulated in circumstances of low Fe intake [27] and hyperglycemia conditions [59]. We have no evidence of differences in the Fe content or glycemic levels among experimental diets; therefore, the reason why the SDP-PDP treatment increased the expression of SLC11A2/DMT1 should be researched further.…”
Section: Discussionmentioning
confidence: 95%